Related factors of the nutritional status of malnutrition in Cham ethnic children aged 6-24 months - Tran, Quang Hien (International Journal of Contemporary Pediatrics, 2024)
Background: This study aims to identify factors related to the nutritional status of children aged 6-24 months of the Cham ethnic group in Tan Chau town, An Giang province in 2018. Methods: It was a cross-sectional study. Cham ethnic children aged from 6 to 24 months at the time of the survey and their mothers living in Tan Chau town, An Giang province were included in the study as subjects. Results: In the underweight group, the risk of malnutrition for subsequent children is 2.5 times higher compared to the first-born children in the family, and this difference is statistically significant with p<0.05. Among the underweight, stunted, and wasted groups, children with a birth weight of less than 2500 grams have a higher rate of malnutrition compared to those with a birth weight of 2500 grams or more, but this difference is not statistically significant with p>0.05. In the underweight and wasted groups, children who frequently fall ill have a higher rate of malnutrition compared to those who do not fall ill often; however, this difference is not statistically significant with p>0.05. No correlation has been found between the presence of congenital disabilities and the condition of stunting in children with p>0.05. Conclusions: Several factors related to the personal lives of Cham ethnic children aged 6-24 months contribute to the state of malnutrition. It is necessary to enhance communication and counseling efforts to help reduce the malnutrition rate among children in the area as well as within the community.